3D Mapping of NSW Project: Sydney-Gunnedah Basin. Issue 1 (1st December 2018) - Davidson, John; Oliveira, Felipe
Abstract : The Geological Survey of NSW (GSNSW) has created a 3D geological model of the Sydney-Gunnedah Basin that includes best available geological mapping and new 3D modelling. The onshore Sydney Basin comprises the southern section of the Permo-Triassic Sydney-Gunnedah-Bowen system, which overlies the Lachlan Orogen and Late Carboniferous volcaniclastic rocks. The Hunter-Bowen Orogeny formed the adjacent New England Orogen and resulted in uplift and erosion that deposited Jurassic sedimentary sequences of the Surat Basin over large parts of the Gunnedah Basin. Model generation followed GSNSW's map development workflow, developed as part of the larger project: 3D Mapping of NSW. The integrated Sydney-Gunnedah Basin 3D model was developed with the aim of advancing the understanding of the geological and structural setting of the region. This will inform areas of investigation such as coal and hydrocarbon prospectivity, groundwater management and exploration, and environmental and land use decision making.